Ocular Surface Disease Severity in Polycystic Ovary Syndrome: is This Really Significant in Daily Life? - Demet Yabanoglu; Funda Gode (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The purpose of this study was to ascertain the extent to which the ocular surface of women with polycystic ovary syndrome is impacted.